Penerapan Data Mining Menggunakan Algoritma K-Means Untuk Clustering Perokok Usia Lebih dari 15 Tahun - Suharmanto; Wiranti Sri Utami; Nila Pratiwi; Faisal Muhammad (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Smoking is an activity that can have a bad impact on health, both for yourself and for others. This is because there are various kinds of ingredients that are dangerous to health, there are 4000 types of chemicals found in cigarettes, starting from nicotine and other substances that can cause cancer in humans. The dataset obtained from BPS (Central Statistics Agency) can be utilized by using K-Means Clustering to determine the grouping of smokers aged more than 15 years in each region. The grouping of smokers aged over 15 years can be seen through 3 clusters, Cluster 1 is the highest level of smoking in 10 provinces out of 34 provinces studied, Cluster 2 is the medium level with 15 provinces out of 34 provinces studied, and Cluster 3 is the lowest level. with 9 Provinces.